EKSISTENSI PARTAI PERSATUAN DAYAK PADA PEMILU 1955 - Rikaz Prabowo (SWADESI: Jurnal Pendidikan dan Ilmu Sejarah, 2020)
This Research aims to describe: (1) Dayak political awakening before election 1955 (2) The struggle PPD in the face of election 1955, (3) Impact PPD post-election victory 1955. This study uses a critical history method. Based on the results of the research can be concluded: first, the political movement of Dayak society, especially in West Kalimantan, began to rise after the proclamation independence of Indonesia with the founding of Dayak In Action (DIA) on 3 November 1945. He was later changed to PPD on 30 November 1946. Secondly, The PPD also conducts consolidation and cadre, maximizing the grassroots potential of the Dayak community, as well as conducting the campaigns in areas.Third, PPD successfully won the 1955 election and occupied strategic positions of government in both the executive and legislative . PPD also sent his deputy for DPR-RI and constituency. In addition, PPD managed to deliver J. C Oevaang Oeray was elected as the Governor of the regional head of West Kalimantan.